Use of a platysma myocutaneous flap for the reimplantation of a severed ear: experience with five cases - Mello-Filho, Francisco Veríssimo de; Mamede, Rui Celso Martins; Koury, Adilon Passinho (São Paulo Medical Journal, 1999)
CONTEXT: The traumatic loss of an ear greatly affects the patient because of the severe aesthetic deformity it entails. The characteristic format of the ear, with a fine skin covering a thin and elastic cartilage, is not found anywhere else in the human body. Thus, to reconstruct an ear, the surgeon may try to imitate it by sculpting cartilage and covering it with skin. OBJECTIVE: To use a platysma myocutaneous flap for the reimplantation of a severed ear in humans. DESIGN: Case report. SETTING: Emergency unit of the university hospital, Faculty of Medicine, Ribeirão Preto - USP. CASE REPORT: Five cases are reported, with whole ear reimplantation in 3 of them and only segments in 2 cases. The surgical technique used was original and was based on the principle of auricular cartilage revascularization using the platysma muscle. We implanted traumatically severed auricular cartilage into the platysma muscle. The prefabricated ear was later transferred to its original site in the form of a myocutaneous-cartilaginous flap. Of the 5 cases treated using this technique, 4 were successful. In these 4 cases the reimplanted ears showed no short- or long-term problems, with an aesthetic result quite close to natural appearance. In one case there was necrosis of the entire flap, with total loss of the ear. The surgical technique described is simple and utilizes the severed ear of the patient. Its application is excellent for skin losses in the auricular region or for the ear itself, thus obviating the need for microsurgery or the use of protheses or grafts.